1988
DOI: 10.1111/j.1439-0396.1988.tb00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the beta‐agonist cimaterol on blood metabolite and hormone concentrations, growth and carcass composition in finishing friesian steers

Abstract: Zusammenfassung Der Einfluß des Beta‐Agonisten Cimaterol auf einige Blutmetaboliten und Hormonkonzentrationen im Blut, Wachstum und Schlachtkörperzusammensetzung von Schwarzbunten Ochsen Es wurde der Einfluß des Beta‐Agonisten Cimaterol auf die Mastleistung während der Endmastphase und die Schlachtkörperzusammensetzung von Schwarzbunten Ochsen untersucht. 4 Gruppen mit jeweils 15 Tieren erhielten über einen Versuchszeitraum von 91 Tagen Grassilage ad libitum + 4 kg eines pelletierten Kraftfutters pro Tier und … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
8
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
4
8
0
1
Order By: Relevance
“…The improvement of the carcass characteristics and the reduction of the weight of organs are in agreement with the findings previously observed in cattle Williams et al, 1987;Miller et al, 1988;Quirke et al, 1988) and sheep (Thornton et al, 1985;Kim et al, 1989). Reductions of the viscera were reported by Williams et al (1987) and Quirke et al (1988).…”
Section: Fortysupporting
confidence: 81%
See 2 more Smart Citations
“…The improvement of the carcass characteristics and the reduction of the weight of organs are in agreement with the findings previously observed in cattle Williams et al, 1987;Miller et al, 1988;Quirke et al, 1988) and sheep (Thornton et al, 1985;Kim et al, 1989). Reductions of the viscera were reported by Williams et al (1987) and Quirke et al (1988).…”
Section: Fortysupporting
confidence: 81%
“…Rumen fermentation characteristics were calculated by analysis of variance in a repeated measures experiment (Snedecor and Cochran, 1980 in Friesian veal calves (Williams et al, 1987) or in crossbred heifers (Miller et al, 1988 (Quirke et al, 1988). Reeds et al (1986) (Stiles et al, 1984).…”
Section: Fortymentioning
confidence: 99%
See 1 more Smart Citation
“…Com relação ao tecido adiposo, observa-se a diminuição da gordura corporal, particularmente a subcutânea e a intermuscular, em decorrência do uso de ractopamina em dietas para suínos (Willians et al, 1994;Carr et al, 2005), principalmente em virtude do efeito antilipogênico deste agonista (Quirke et al, 1988;Peters, 1990;Haese e Bünzen, 2005). Entretanto, em função destes mesmos efeitos metabólicos, a ractopamina também pode afetar as características qualitativas da carne, sendo um importante aspecto a ser considerado, tanto para a indústria quanto para o consumidor.…”
Section: Introductionunclassified
“…1987), although the mode of action is not always clear (Fiems 1987). A considerable hypertrophy, especially of the hindquarters, was observed in cimaterol-fed steers (Quirke et al 1988); this may be provoked by improved nitrogen retention (Fiems et al 1990). Reports from Wheeler and Koohmaraie (1992) and Chikhou et al (1993) showed strong evidence that shear force values were increased after the administration of Bagonists to cattle.…”
mentioning
confidence: 99%